Evaluation of cocoa husk biochar in the bean (Vigna unguiculata, L.) var. Lina (Original) (REDEL. Revista Granmense de Desarrollo Local, 2023)
Cuban economic policy in agriculture aims to increase cocoa crop productions, which implies an increase of biomass residues and the need to find a suitable use for their disposal.  This article evaluates the effects of cocoa husk biochar on the bean (Vigna unguiculata, L.) var. Lina. The results obtained indicated the presence of high contents of carbon, calcium, potassium, nitrogen and oxygen, which makes it a suitable candidate to be used as a soil fertilizer and the conversion into value-added products through the slow pyrolysis process, thus contributing to environmental protection, reducing the greenhouse effect and generating additional income for farmers in rural populations.
Keywords: biomass; pyrolysis; biochar; cocoa